A simple imaging‐based technique for quantifying haze and transmittance of materials. Issue 3 (19th April 2017) - Busato, Stephan; Perevedentsev, Aleksandr
Abstract : We present a simple technique for measuring haze and transmittance of materials that uses inexpensive and virtually ubiquitous hardware, and is based on photographic imaging of at least partially transparent samples backlit through a "knife‐edge" array mask. Its performance is tested for a series of injection‐molded polyethylene plaques containing a varied fraction of a clarifying agent, as well as commercially available ASTM D1003 haze standards. The results show excellent agreement with those obtained using a conventional haze meter adhering to the ASTM D1003 standard and, moreover, are specifically indicative of the overall contact haze—a desirable feature for characterization of, for instance, commodity plastics for packaging applications. Notably, the quantification of haze is based explicitly on the reduction of perceived image quality of objects viewed through a material sample and, hence, quantifies haze in a more practically useful way compared with the, arguably, more arbitrary ASTM definition. The demonstrated technique can be further used to extract more sophisticated, local information on the microstructure and optical properties, which cannot be obtained with a conventional haze meter. Its potential for being standardized, as well as additional modifications that can enable improved performance, are also discussed. POLYM. ENG. SCI., 58:345–352, 2018. © 2017 Society of Plastics Engineers